ENVIRONMENTAL SANITATION AND DIARRHEA IN CHILDREN AGES 12-59 MONTHS IN POJOK VILLAGE, BOJONEGORO, INDONESIA: Hubungan Sanitasi Lingkungan dengan Diare Pada Anak Usia 12-59 Bulan di Desa Pojok, Purwosari, Bojonegoro, Jawa Timur, Indonesia - Syaiful Imam Gozali; Erni Astutik; Wan Ismahanisa Ismail (Universitas Airlangga, 2023)
Background: Diarrhea is caused by infection, malabsorption, and food consumption. Based on the results of the Indonesian Basic Health Research (Riskesdas) in 2018, the frequency of diarrhea in Indonesian people diagnosed by health workers is 6.80%. Purpose: This study aimed to determine the relationship between environmental sanitation and diarrhea in children aged 12-59 months in Pojok Village, Purwosari District, Bojonegoro Regency. Methods: This study used analytical observations from a Cross-Sectiononal design. The sampling method used was total sampling. The population for this study consisted of mothers with children aged 12-59 months, as many as 24 people in the village of Pojok in the Purwosari district of Bojonegolo Regency in 2020. The statistical test used Chi-Square with computer software. Results: The results showed that respondents who did not have healthy latrines had a higher risk of developing diarrhea than those who had healthy latrines (PR = 2.60, 95% CI = 1.01-6.69, p = 0.02). Respondents who did not have closed SPAL had a higher risk of developing diarrhea than those who had closed SPAL (PR = 3.10, 95% CI = 1.19-8.07, p = 0.00). Respondents who did not have a closed trash can had a higher risk of experiencing diarrhea than those with a closed trash can (PR = 3.50, 95% CI = 1.40-11.79, p = 0.00).Conclusion: In this study, there was a significant association between healthy latrine availability, SPAL availability, and trash availability variables and the incidence of diarrhea in children aged 12-59 months in the village of the Pojok Purwosari district of Bojonegoro. Kata kunci : Sanitasi, Diare, Kematian anak, Kesehatan Masyarakat Diarrhea is watery defecation more than three times a day, with or without blood and/or mucus in the stool. Diarrhea is caused by infectious factors, malabsorption (impaired absorption of nutrients), food and psychological factors. In developing countries, including Indonesia, children suffer from diarrhea more than 12 times per year and this is the cause of death by 15-34% of all causes of death. The purpose of this study was to determine the relationship between environmental sanitation and diarrhea in children aged 12-59 months in Pojok Village, Purwosari District, Bojonegoro Regency. The type of research used is analytic observational research using cross sectional research methods. The sampling technique used was total sampling. The population and sample in the study were all mothers with children aged 12-59 months who were in Pojok Village, Purwosari District, Bojonegoro Regency in 2020 as many as 24. Statistical tests using Chi Square with the help of computer software. The results of the study showed that respondents who did not have healthy latrines (PR = 2,600, 95% CI = 1,011-6.689, p = 0.021), not having a closed SPAL (PR = 3.095, 95% CI = 1.188-8.066, p=0.002), and not having a closed waste bin (PR = 3.500, 95% CI = 1.039-11.789, p=0.005) had a higher risk of having children with diarrhea in the last 2 weeks. It was concluded that there was a significant relationship between the variables of availability of healthy latrine, availability of SPAL, and availability of trash cans with the incidence of diarrhea in children aged 12-59 months in Pojok Village, Purwosari District, Bojonegoro Regency. Researchers suggest making clean water sources in accordance with established procedures, making healthy latrines, making closed garbage boxes and making waste water disposal channels as well as optimizing environmental health socialization programs, namely prevention and control of diseases. Keywords: Water & sanitation and hygiene, Diarrhea, Child Mortality, Public Health